Bounds on Negative Binomial Approximation to Call Function - Amit N. Kumar (Revstat Statistical Journal, 2024)
In this paper, we develop Stein's method for negative binomial distribution using call function defined by fz(k) = (k - z)+ = max{k - z, 0}, for k ≥ 0 and z ≥ 0. We obtain error bounds between E [ fz(Nr,p)] and E [ fz(V )], where Nr,p follows negative binomial distribution and V is the sum of locally dependent random variables, using certain conditions on moments. We demonstrate our results through an interesting application, namely, collateralized debt obligation (CDO), and compare the bounds with the existing bounds.